Functional reorganization in the developing lexicon: separable and changing influences of lexical and phonological variables on children's fast-mapping*. Issue 2 (20th January 2012) - MCKEAN, CRISTINA; LETTS, CAROLYN; HOWARD, DAVID
ABSTRACT: Neighbourhood Density (ND) and Phonotactic Probability (PP) influence word learning in children. This influence appears to change over development but the separate developmental trajectories of influence of PP and ND on word learning have not previously been mapped. This study examined the cross-sectional developmental trajectories of influence of PP and ND on fast-mapping in thirty-eight English-speaking children aged 3 ; 01–5 ; 02, in a task varying PP and ND orthogonally. PP and ND exerted separable influences on fast-mapping. Overall, low ND supported better fast-mapping. The influence of PP changed across the developmental trajectory, 'switching' from a high to a low PP advantage. A potential explanation for this 'switch' is advanced, suggesting that it represents functional reorganization in the developing lexicon, which emerges from changes in the developing lexicon, as phonological knowledge is abstracted from lexical knowledge, over development.